2021
DOI: 10.15809/irriga.2021v1n4p730-738
|View full text |Cite
|
Sign up to set email alerts
|

Uso De Cobertura Morta E Água Salina Na Produtividade Da Cultura Do Milho

Abstract: USO DE COBERTURA MORTA E ÁGUA SALINA NA PRODUTIVIDADE DA CULTURA DO MILHO     GEOVANA FERREIRA GOES1, GEOCLEBER GOMES DE SOUSA2, CARLA INGRYD NOJOSA LESSA3, FRED DENILSON BARBOSA DA SILVA2, CLAUDIVAN FEITOSA DE LACERDA4, RAFAELLA DA SILVA NOGUEIRA2   1Graduanda no curso de Agronomia da Universidade da Integração Internacional da Lusofonia Afro-Brasileira (Avenida da Abolição, 3, centro, 62.790-000, Redenção/Ce, Brasil). E-mail: ggoes64@gmail.com 2Professores Doutores, Instituto de Desenvolvimento Rural, Agron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Similar trends to the present study were described by Goes et al (2021) working with corn crop in soil mulch with spontaneous plants inserted during the reproductive phase, where irrigation with lower salinity water in the presence of mulch provided a yield of 4,220 kg ha -1 . On the other hand, Rodrigues et al (2020) recorded a productivity below (1,523 kg ha -1 ) that found in this study when using brackish water on corn crop in soil without vegetal mulch.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Similar trends to the present study were described by Goes et al (2021) working with corn crop in soil mulch with spontaneous plants inserted during the reproductive phase, where irrigation with lower salinity water in the presence of mulch provided a yield of 4,220 kg ha -1 . On the other hand, Rodrigues et al (2020) recorded a productivity below (1,523 kg ha -1 ) that found in this study when using brackish water on corn crop in soil without vegetal mulch.…”
Section: Resultssupporting
confidence: 91%
“…the soil during the reproductive phase were also found by Goes et al (2021). These same authors concluded that the use of weed mulching in the reproductive phase of corn crop irrigated with 3.0 dS m -1 brackish water provided similar effect as in the present study.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations